\(R\)-Complex Finsler Spaces With Generalized Kropina Metric
The study of \(R\)-complex Finsler spaces with an \((α, β)\)-metric is a fundamental problem in Finsler geometry. In this paper, we introduce the concept of \(R\)-complex Finsler spaces with a generalized Kropina metric given by \(F = α^m+1 β^m\). We derive explicit formulas for the fundamental metric tensor fields \(g_ij\) and \(g_ij \), as well as their determinants and inverse tensor fields for this metric. Additionally, we discuss various properties of non-Hermitian \(R\)-complex Finsler spaces with the aforementioned metric. , number=1, journal=Communications in Mathematics and Applications, author=Renu and Kushwaha, Ramdayal Singh, year=2024, month=Apr., pages=243–252